The Prevalence of Urinary Incontinence in Pregnant Women A Cross-Sectional Study - Azra.A.Ghani, Siraj Ul Islam, Saima Hamayun, Mohd Ibrahim, Mohd.Shoab, Sami Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of the study was to assess the prevalence of urine incontinence in pregnant women. Study design, Place and Duration: This cross-sectional study conducted at the department of urology LRH hospital Peshawar from January 2021 to July 2021, over a six-month duration. Methodology: After 26 weeks of pregnancy, as determined by either the woman’s LMP (last menstrual period) or an ultrasound performed in the first trimester, a random sample of 160 healthy pregnant women was questioned and their responses were recorded on a proforma. Urinary incontinence, renal failure, diabetes, and gestational diabetes were all conditions that disqualified women from inclusion in the study. Interview data was used as the primary method of assessing the prevalence of urine incontinence among pregnant women. SPSS 22.0 was used to analyze the data. Results: The prevalence of urinary incontinence was 45%, with 74 out of 160 women reporting it. Of them, 58 had stress incontinence (SI), and 15 experienced urge incontinence. Overall, 36% of people have SI whereas just 9% have UI. Of the 65 first-time mothers who took part in the trial, 26 had urine incontinence. In the third trimester of pregnancy, 45 percent of women had UI. Practical implication: By raising the level of awareness of urinary incontinence among medical personnel caring for pregnant patients, the findings will aid in the development of more comprehensive training programmes to prevent incontinence during pregnancy. Conclusion: Urinary incontinence is quite common during pregnancy. The findings will aid in increasing healthcare providers’ awareness of urine incontinence while treating pregnant patients and in the development of more thorough education campaigns to avoid pregnancy-related incontinence. We recommend regular pelvic floor exercises for all pregnant women. Keywords: Prevalence of Urinary Incontinence,Stress urinary incontinence, urinary incontinence, Pregnant Women